The Role of Social Entrepreneurs in Transforming Yemen's Agricultural Landscape - Al-Awadhi, Ahad Lutf; Ritonga, Alwi Dahlan (Talenta Publisher, 2024)
Social entrepreneurship in Yemen offers innovative solutions to agricultural challenges amidst economic and social crises. By integrating sustainability and community empowerment, the program addresses issues such as land degradation, climate change, and food security and fosters local economic resilience and self-reliance. This research aims to analyze the role of social entrepreneurship in transforming Yemen's agricultural sector, addressing economic challenges, environmental degradation, and social vulnerability due to conflict. This research method uses a descriptive-analytical approach. The data collection technique is a literature study conducted by collecting data from various written sources such as books, scientific journals, articles, research reports, and relevant policy documents. The data analysis technique applied in this research is descriptive qualitative analysis. Social entrepreneurship is crucial in transforming Yemen's agricultural sector, addressing economic challenges, environmental degradation and social vulnerability due to conflict. Initiatives such as organic farming, cooperative management, and the adoption of innovative technologies sustainably increase agricultural productivity. In addition, social entrepreneurship supports the digitalization of agriculture through programs that provide access to real-time information and energy-saving technologies. For example, the Barq Foundation helps farm management, reduces operational costs, and improves food security. The study concludes that social entrepreneurship strengthens sustainable development and food security in Yemen.